Analysis of Internal and External Factors after Implementing the Improvement Strategy using SWOT Method - Prima Vitasari (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Every businessman is expected to have knowledge and strategies in managing the company so that they can survive. Especially in small and medium enterprises (SME), a kind of business of this traditional cloth product. The problem is that SMEs have difficulty in increasing sales of their products. This study presents an internal and external analysis after the implementation of the improvement strategy. The method used was a survey to collect data. A total of one hundred consumers participated in this study. The results of the analysis show an increase in the calculation of the strength and opportunity factors, a decrease in the points of weakness and threat factors. The total calculation shows an increase in efforts to provide a sales improvement strategy. Meanwhile, the calculation for each point resulted in an increase of fourteen points in both internal and external factors as a whole. The results of the quadrant position analysis also show that SME is in a very profitable position by having strengths and opportunities. SME has a favorable position in the form of skilled human resources, sufficient capital, and a promising market for this product. From these results, it is hoped that SME will continue to make continuous improvements by utilizing the strengths and opportunities they have. For further research, it can examine the focus on priority improvements, namely product, promotion and implementation in depth